Understanding how world-class competitive swimming coaches learn to coach - Mc Carthy, E. (Journal of Swimming Research, 2020)
BACKGROUND: Learning to become a world-class swimming coach is a complicated process. There is little consensus on how coaches learn and therefore the purpose of this research is to qualitatively investigate the learning sources of coaches, identify potential gaps in the coach development process and suggest possible solutions. METHODS: Coaches, at both national and international level (n=16), were asked to participate in semi-structured interviews. Grounded Theory was used to analyze the interviews and investigate the personal learning experiences of the coaches. RESULTS: For swimming coaches there are two main learning pathways, namely, formal and informal. The most effective pathway is informal, consisting of mentorship, peer learning, self-reflection and life experience; while formal certification is the least effective learning pathway. In addition, the quality of mentor and peer group access is of a higher standard amongst world-class coaches in comparison to national level coaches. CONCLUSION: In learning to become world-class, a coach should follow informal pathways rather than relying on formal certification courses. National governing bodies and coach education programs should focus on providing coach education through informal methods and in particular the use of expert mentorship programs.